2011
DOI: 10.1002/joc.2346
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of land‐use/land‐cover changes on the near‐surface atmosphere in southern South America

Abstract: ABSTRACT:A fully coupled atmospheric-biospheric regional climate model, GEMRAMS, was used to evaluate potential effects of land-use/land-cover changes (LULCC) on near-surface atmosphere over a southern South American domain at seasonal time scales. In GEMRAMS, leaf area index and canopy conductance are computed based on modelled temperature, solar radiation, and the water status of the soil and air, allowing a two-way interaction between canopy and atmosphere. Several austral spring-early summer simulations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 72 publications
6
51
0
Order By: Relevance
“…However, the induced changes in temperature, convective available potential energy, and precipitation over the region are of the same order of magnitude as those found in other modeling studies on landatmosphere interactions over southern South America (e.g., Beltrán-Przekurat et al 2012;Lee and Berbery 2012;Müller et al 2014), and the overall statistical significance is similar to the results by Beltrán-Przekurat et al (2012) and Lejeune et al (2015). This suggests that, although land processes have a detectable effect on the atmosphere, this effect is within the variability of atmospheric variables.…”
Section: Summary and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, the induced changes in temperature, convective available potential energy, and precipitation over the region are of the same order of magnitude as those found in other modeling studies on landatmosphere interactions over southern South America (e.g., Beltrán-Przekurat et al 2012;Lee and Berbery 2012;Müller et al 2014), and the overall statistical significance is similar to the results by Beltrán-Przekurat et al (2012) and Lejeune et al (2015). This suggests that, although land processes have a detectable effect on the atmosphere, this effect is within the variability of atmospheric variables.…”
Section: Summary and Discussionsupporting
confidence: 75%
“…The largest sensitivity to the effects of the groundwater scheme are found in parts of the La Plata basin, where previous studies have shown a substantial sensitivity of atmospheric conditions, including precipitation, to characteristics and dynamics of the soil moisture field (e.g., Saulo et al 2010), land-use and land-cover change (Beltrán-Przekurat et al 2012;Lee and Berbery 2012), land-cover and vegetation properties (Lee et al 2013;Müller et al 2014), soil texture properties (e.g., Doyle et al 2013), and the coupling between soil moisture and precipitation (e.g., Zeng et al 2010;Sörensson and Menéndez 2011;Spenneman and Saulo 2015). This study, along with other previous studies, suggests that the climate of southern South America is particularly sensitive to surface and subsurface hydrological conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, they could also mean that the soil moisture initialization might have influenced the intensity of the impacts of land-use change by preventing larger modifications of the total available energy and affecting its partition into latent and sensible heat fluxes. Beltrán-Przekurat et al (2012) evaluated the sensitivity of landcover change impacts to initial soil moisture in southern South America and found that wetter (drier) initial conditions tended to lessen (amplify) the response of temperature and precipitation, although for the latter, wetter conditions could also have the opposite effect depending on the region. Moreover, the aforementioned study also found that the sensitivity was not too large for the case of temperature but it could be as large as the impact of land-use change for the case of precipitation.…”
Section: Near-surface Temperature and Precipitationmentioning
confidence: 99%
“…However, only a few studies have addressed the topic in southern South America, where extensive land-use change has occurred in recent decades: Beltrán-Przekurat et al (2012) performed a series of regional numerical simulations to evaluate the potential effects of land-use change on the near-surface atmosphere at the seasonal scale. Lee and Berbery (2012) carried out multiple 3-month numerical experiments using the atmosphere-land coupled WRF-Noah model to assess the potential regional impacts of land-cover change in the La Plata River Basin on precipitation and near-surface temperature during spring.…”
Section: Introductionmentioning
confidence: 99%
“…Beltran-Przekurat et al [16] performed some interesting simulations based on South America with their scenarios of land use, agriculture, grasslands and afforested areas. They were performed for three separate sets of El Nino -Southern Oscillation conditions.…”
Section: Exponential Smoothingmentioning
confidence: 99%